Reaction with N,N-diethyl-p-phenylenediamine: A procedure for the sensitive square-wave voltammetric detection of chlorine - Seymour, E; Lawrence, N; Compton, R (2003)
The reaction of chlorine and N,N-diethyl-p-phenylenediamine has been studied as a means of generating an analytical voltammetric signal of much improved sensitivity and selectivity for the detection of the former than is possible via direct electrolysis. A reaction mechanism is suggested whereby the chlorine attacks the primary amine of DEPD to form the N-chlorinated product that shows a much enhanced signal under conditions of square-wave voltammetry than does chlorine itself. The analytical parameters were found to vary with concentration of DEPD and a linear range from 17 to 495 μM was achievable with a corresponding limit of detection of 6.8 μM.